Volatiles from the xylarialean fungus Hypoxylon invadens - Dickschat, Jeroen S.; Wang, Tao; Stadler, Marc (Beilstein Journal of Organic Chemistry, 2018)
The volatiles emitted by agar plate cultures of the xylarialean fungus Hypoxylon invadens were investigated by use of a closed loop stripping apparatus in combination with GC–MS. Several aromatic compounds were found that could only be identified by comparison to all possible constitutional isomers with different ring substitution patterns. For the set of identified compounds a plausible biosynthetic scheme was suggested that gives further support for the assigned structures.
Keywords: constitutional isomerism; gas chromatography; mass spectrometry; natural products; volatiles